PENGELOLAAN KONTEN INSTAGRAM SEBAGAI MEDIA PROMOSI PARIWISATA RIAU - Untsadewan, Qazza Nakia; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The development of technology has made the Riau Province Tourism Office use Instagram to promote tourism. The goal of this research is to understand how Instagram content management is carried out by the Riau Province Tourism Office in promoting Riau tourism. The research method used in this research is descriptive qualitative. Data was collected through interviews, observation and documentation. The research results show that Instagram content management is in accordance with Chris Heuer's 4C theory: (1) Context: messages are delivered in photo and video format with captions, (2) Communication: information is delivered in a persuasive manner about destinations and events in Riau, (3) Collaboration: active relationships with followers and collaboration with other Instagram accounts, (4) Connection: always innovating and trending in packaging content and regularly uploading to maintain connections with followers. Keywords: Management, Content, Instagram, Promotion, Tourism.